PENGARUH TRANSPARANSI DAN AKUNTABILITAS PENGELOLAAN KEUANGAN TERHADAP KINERJA TENAGA PENDIDIK SMPN 21 DENGAN GAYA KEPEMIMPINAN SEBAGAI VARIABEL PEMODERASI (Manajemen & Bisnis Jurnal, 2022)
This study aims to evaluate the effect of financial management transparency and accountability on the performance of education personnel with leadership style as a moderating variable at 21 SMPN 21 Kota Malang. The population in this study amounted to 50 people with a sampling technique using saturated samples where all populations were sampled. The results of this study indicate that financial management transparency affects the performance of education personnel, financial management accountability affects the performance of education personnel, leadership style affects the performance of education personnel and transparency on the performance of educators through mediation of financial management accountability at State SMPN 21 Kota Malang. Meanwhile, leadership style can moderate the relationship between transparency on the performance of education personnel, leadership style can moderate the relationship between accountability to the performance of education personnel, and leadership style can moderate the relationship between transparency through mediating accountability on the performance of education personnel at SMPN 21 Kota Malang.